The assessment of radio-adaptive response in graves' hyperthyroidism patients following radioactive iodine uptake - Zahra Fazeli; Ali Monfared; Seyed Zakavi; Mehrangiz Amiri; Ebrahim Zabihi; Sajad Borzoueisileh; Amir Gholami; Kourosh Gorji (World Journal of Nuclear Medicine)
Low doses of radiation affect the response of cells to higher doses; this phenomenon is called radio-adaptive response, which leads to increased resistance to subsequent higher doses. We have investigated the adaptive response using 0.37 MBq priming dose of I-131 followed by 296–444 MBq challenging dose in peripheral human lymphocyte cells. The study was performed on 42 patients with Graves' disease and 29 healthy adult persons as a control group. The patients were divided into two groups. In the first group, patients were referred for radioactive iodine therapy with a specific dose, and iodine was given to them on the day of referral. In the second group, patients were referred for radioactive iodine uptake and radioactive iodine therapy, and iodine uptake was initially performed, then 24 h later, iodine therapy was done. In both groups, 1 month after treatment, blood samples were taken to cytokinesis-block micronucleus (MN) assay. The number of MN in binuclear lymphocyte cells was counted as an end point test. The mean frequency of MN in first, second, and control groups was 75.86 ± 12.68, 71.45 ± 12.56, and 20.06 ± 7.30, respectively. Our results showed that the frequency of total chromosome aberration in both radiation groups was higher than controls. However, in the first group was higher than another group, but their difference was not statistically significant. According to the results, we cannot approve the hypothesis that 0.37 MBq I-131 administration before iodine therapy could induce a radio-adaptive response in lymphocytes of Graves' patients.